ANALYSIS OF THE EFFECT OF COMMUNICATION INTENSITY AND FEEDBACK ON RESELLER LOYALTY WITH BUSINESS RELATIONSHIP QUALITY AS AN INTERVENING VARIABLE (CASE STUDY ON DEENSCARF HIJAB) - Dewi, Dinda Thalia; Antonio, Tony (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The research aims to see the effect of communication intensity and feedback on the loyalty of resellers of Deenscarf hijab products which is mediated by the quality of business relationships. The research is quantitative by adopting a type of causal research, namely knowing the influence or causal relationship between the independent variables (intensity of communication and feedback) and the dependent variable (reseller loyalty) through an intervening variable (quality of business relationships). The sampling technique used a total sampling of 117 respondents. Data collection was carried out by distributing questionnaires to all samples who were resellers of Deenscarf hijab products. Data analysis was carried out with Partial Least Square (PLS) using SmartPLS 4 software to see the direct and indirect effects between variables. The research results show that the intensity of communication, feedback and the quality of business relationships have a direct and significant effect on the loyalty of resellers of Deenscarf hijab products. The intensity of communication and feedback has a direct and significant effect on the quality of Deenscarf's business relationships with its resellers. Indirectly, the quality of business relationships significantly mediates the influence of communication intensity and feedback on the loyalty of resellers of Deenscarf hijab products.